2020
DOI: 10.1016/j.econmod.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Food security in Kenya: Insights from a household food demand model

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The mean DDS among the children in our study (2•5) is nearly half of the recommended minimal DDS of 4 (42) , and many children were not fed any meals, especially in the youngest age group, showing that both the DDS and meal frequency were insufficient to meet children's dietary needs. Although the results from the FGD suggested that a few mothers had learned to re-allocate their food budgets to better follow what they were learning from the videos, poverty remains a major barrier for proper complementary feeding in Africa (1,43) , with a third of Kenyans living in food poverty (44) . However, complementary feeding education has been shown to improve child growth parameters, even in food insecure areas (45) , indicating that efforts should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…The mean DDS among the children in our study (2•5) is nearly half of the recommended minimal DDS of 4 (42) , and many children were not fed any meals, especially in the youngest age group, showing that both the DDS and meal frequency were insufficient to meet children's dietary needs. Although the results from the FGD suggested that a few mothers had learned to re-allocate their food budgets to better follow what they were learning from the videos, poverty remains a major barrier for proper complementary feeding in Africa (1,43) , with a third of Kenyans living in food poverty (44) . However, complementary feeding education has been shown to improve child growth parameters, even in food insecure areas (45) , indicating that efforts should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, land management [ 7 ], advanced biotechnologies [ 8 ], and water management [ 9 ] were used to improve agricultural efficiency. Increasing the financial statement of households (e.g., Reference [ 10 ]) through new policies to raise the level of education [ 11 ] has also shown promising results. Interdisciplinary research has provided valuable findings in the fight against food insecurity, one of which is social capital [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, land management [7], advanced biotechnologies [8], and water management [9] were used to improve agricultural efficiency. Increasing the financial statement of households (e.g., Reference [10]) through new policies to raise the level of education [11] has also shown promising results. Interdisciplinary research has provided valuable findings in the fight against food insecurity, one of which is social capital [12,13].…”
Section: Introductionmentioning
confidence: 99%